1994
DOI: 10.1007/bf00378532
|View full text |Cite
|
Sign up to set email alerts
|

The force-velocity relation of the rabbit inferior oblique muscle; influence of temperature

Abstract: The contractile properties of the rabbit inferior oblique muscle (IO) were studied in vitro with direct stimulation at temperatures between 20 and 35 degrees C. Isovelocity releases were used to determine the force/velocity relation. Cooling the muscle from 35 degrees C to 20 degrees C increased contraction and half-relaxation times of single twitches with a temperature coefficient (Q10) of 0.4, but did not affect significantly the twitch tension. The tetanic tension increases with increasing temperature (Q10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 20 publications
5
39
0
Order By: Relevance
“…The Q 10 for V max was 1.6 for temperatures between 25.6 and 37.1°C, which is in good agreement with studies of non-human muscle [3,6,22,27]. The most likely explanation for the decrease of V max with muscle cooling is a decreased activity of the actomyosin adenosine triphosphatase (ATPase) [35], which is the most important determinant of shortening velocity [5].…”
Section: Maximal Shortening Velocitysupporting
confidence: 69%
“…The Q 10 for V max was 1.6 for temperatures between 25.6 and 37.1°C, which is in good agreement with studies of non-human muscle [3,6,22,27]. The most likely explanation for the decrease of V max with muscle cooling is a decreased activity of the actomyosin adenosine triphosphatase (ATPase) [35], which is the most important determinant of shortening velocity [5].…”
Section: Maximal Shortening Velocitysupporting
confidence: 69%
“…In a previous comparison, Frueh and colleagues (2001) found that muscle force (force per cross-sectional area, kN/m 2 ) measured in situ were about six times greater than the highest of those reported previously for extraocular muscles in vitro (Close and Luff, 1974;Asmussen and Gaunitz, 1981;Luff, 1981;Asmussen et al, 1994;Frueh et al, 1994). Our own lab has reported force measurements of the superior oblique muscle obtained in situ to be 3 to 6 times greater than that of the same muscle in vitro (Chen and von Bartheld, 2004;Croes et al, 2007).…”
Section: Parameters That Compromise Contractile Force Measurements Inmentioning
confidence: 81%
“…Q 10 >2 (where the temperature coefficient Q 10 is the factor by which a rate increases with a 10°C increase in temperature). This marked decline has been found in a diversity of muscles from a vast array of animals, including vertebrates and invertebrates, endotherms and ectotherms (Putnam and Bennett, 1982;Bennett, 1984;Bennett, 1985;Hirano and Rome, 1984;Renaud and Stevens, 1984;Else and Bennett, 1987;John-Alder et al, 1989;Faulkner et al, 1990;Stevenson and Josephson, 1990;Barnes and Ingalls, 1991;Rome et al, 1992a;Rome et al, 1992b;Swoap et al, 1993;Asmussen et al, 1994;Sobol and Nasledov, 1994;Altringham and Block, 1997;Choi et al, 1998;Donley et al, 2007;Herrel et al, 2007).…”
Section: Introductionmentioning
confidence: 98%